Baseline characterization of aquaculture systems and livelihoods in the states of Kwara and Nasarawa-Nigeria - Lozano, Denise; Manyise, Timothy; Siriwardena, Sunil; Subasinghe, Rohana; Olaniyi, Ajibola; Ghazali, Saadiah; Rossignoli, Cristiano (WorldFish, 2024)
This report presents the outcomes of the latest research conducted by WorldFish and its partners in their series of studies in Nigeria. The purpose of these studies is to address knowledge gaps about the characteristics of aquaculture systems and livelihoods across different regions of the country. Conducted in areas with significant aquaculture potential, these studies aim to support the sustainable and inclusive development of the sector nationwide.